Exploring the journeys of Hispanic and Latinx women leaders in community colleges: a focus on the intersectionality of gender and ethnicity in leadership - Arca, Vasiliki (My University, 2026)
This qualitative narrative inquiry study explored the lived experiences of Latinx women who held executive positions in community colleges, with particular attention to identity, barriers, and sources of support. Existing research revealed an underrepresentation of Latinx women in executive leadership across community colleges, despite serving increasingly diverse student populations. This disparity highlights a need to understand experiences and contextual factors that influence professional journeys of Latinx women leaders. The study applied intersectionality and leadership identity development theories as its guiding framework to examine how gender and ethnicity intersected to shape the career progression of Latinx women in higher education. An illustrative sample of Latinx women in executive roles across community colleges in various regions of the United States participated in the study. Participants shared their lived experiences through semistructured interviews, offering insights into their pathways to leadership, challenges they faced, and internal and external factors that supported or hindered their advancement. This study contributes to the literature by illuminating how the intersecting identities of gender and ethnicity shape the leadership journeys of Latinx women in community college executive roles, and offers implications for research, leadership development, and institutional policies aimed at advancing equitable and representative leadership in higher education.
Keywords: Intersectionality; Leadership; Latinx; Women; Community colleges; Identity